Rekontruksi Peran Gender pada Pengasuhan Anak-Anak Korban Perceraian di Panti Asuhan Hayat Sabungan Jae - Ritonga, Sylvia Kurnia (Syekh Ali Hasan Ahmad Addary State Islamic University, 2025)
The development of children in orphanages is greatly influenced by the parenting pattern provided by the caregiver as a substitute for the role of the biological father and mother. Divorce as a factor that causes children's development to be hampered both mentally, physically and cognitively. Reconstruction of gender roles is very necessary to produce healthy children, full of potential and self-confident children of divorce victims in orphanages. This study aims to determine the gender reconstruction of parenting at the Hayat Sabungan Jae orphanage in Padangsidimpuan City. This study is a qualitative study, namely looking at gender reconstruction in the care of children who are victims of divorce. Data were collected through observation, interviews, and document studies. The results of this study indicate that parenting practices are carried out by placing caregivers as fathers and mothers who replace their biological parents in three aspects, namely care, education and child self-development. Reconstruction of gender roles in the parenting process is carried out by considering the age of the child by engineering the role of the father and mother as befits the biological mother. The process is carried out by placing the father and mother specifically during the transition from the biological mother and father. Then self-development after adolescence by paying attention to the interests and talents of boys and girls. From the results of this study, it can be concluded that caregiving with gender reconstruction runs full of limitations of caregivers in Hayat orphanages. This means that there needs to be a balanced relationship between foster children and caregivers to create maximum care based on gender.